2015
DOI: 10.1073/pnas.1503779112
|View full text |Cite|
|
Sign up to set email alerts
|

i1 and Gα i3 regulate macrophage polarization by forming a complex containing CD14 and Gab1

Abstract: Heterotrimeric G proteins have been implicated in Toll-like receptor 4 (TLR4) signaling in macrophages and endothelial cells. However, whether guanine nucleotide-binding protein G(i) subunit alpha-1 and alpha-3 (Gαi1/3) are required for LPS responses remains unclear, and if so, the underlying mechanisms need to be studied. In this study, we demonstrated that, in response to LPS, Gαi1/3 form complexes containing the pattern recognition receptor (PRR) CD14 and growth factor receptor binding 2 (Grb2)-associated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…Given the reduced pro-inflammatory responses in LysMCre QKI fl/fl mice after transferring peritoneal macrophages that overexpress QKI5 in the LPS-induced mice model, alternatively activated macrophages (M2) were anticipated. Thus, we measured changes in the proportion of peritoneal M1 macrophages (F4/80 int CD11b int ) and M2 macrophages (F4/80 hi CD11b hi ) ( 35 ). Compared to macrophages in QKI fl/fl mice, an increase in M1 macrophages and a decrease in M2 macrophages were shown in LPS-treated LysMCre QKI fl/fl mice transferred with control cells.…”
Section: Resultsmentioning
confidence: 99%
“…Given the reduced pro-inflammatory responses in LysMCre QKI fl/fl mice after transferring peritoneal macrophages that overexpress QKI5 in the LPS-induced mice model, alternatively activated macrophages (M2) were anticipated. Thus, we measured changes in the proportion of peritoneal M1 macrophages (F4/80 int CD11b int ) and M2 macrophages (F4/80 hi CD11b hi ) ( 35 ). Compared to macrophages in QKI fl/fl mice, an increase in M1 macrophages and a decrease in M2 macrophages were shown in LPS-treated LysMCre QKI fl/fl mice transferred with control cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thymocyte subsets are unperturbed, but splenic and Peyer’s patch B220 + cells are slightly reduced. The report alluded to above (53) showed that TLR4 signaling led to formation of a complex that contained Gα i3, CD14, and Gab1 (growth factor receptor binding 2 (Grb2)-associated binding protein 1), which promoted Akt activation. A deficiency in Gα i3 reduced LPS-induced TLR4 endocytosis and interfered with phosphorylation of interferon regulatory factor 3.…”
Section: Gi Proteinsmentioning
confidence: 99%
“…In contrast to the Gnai2 −/− mice few immune related phenotypes have been reported in the Gnai3 −/− mice although a recent report showed that Gα i3 functions along with Gα i1 in macrophage TLR4 signaling (53). Lymphocytes, neutrophils, and macrophages all express significant levels of Gα i3 yet, chemokine responses are intact in the above cells purified from Gnai3 −/− mice (10,52,54,55).…”
Section: Gi Proteinsmentioning
confidence: 99%
“…Macrophages were derived from bone marrow (BM) as done previously. 7 Briefly, male C57BL/6 mice (8 ~ 12 weeks old) were killed by cervical dislocation, and immersed in 75% of ethanol for 5 minutes. Then, the femur and the tibia were cut off, and the muscles and tissues around them were removed with sterile forceps and scissors.…”
Section: Preparation Of Mouse Primary Bone Marrow-derived Macrophagmentioning
confidence: 99%